FDI and Trade - Two Way Linkages? - Joshua Aizenman; Ilan Noy (University of California, Economics Department, 2005)
The purpose of this paper is to investigate the intertemporal linkages between FDI and disaggregated measures of international trade. We outline a model exemplifying some of these linkages, describe several methods for investigating two-way feedbacks between various categories of trade, and apply them to the recent experience of developing countries. After controlling for other macroeconomic and institutional effects, we find that the strongest feedback between the sub-accounts is between FDI and manufacturing trade. More precisely, applying Geweke (1982)'s decomposition method, we find that most of the linear feedback between trade and FDI (81%) can be accounted for by Granger-causality from FDI gross flows to trade openness (50%) and from trade to FDI (31%). The rest of the total linear feedback is attributable to simultaneous correlation between the two annual series.
Keywords: 330; financial openness; commercial openness; trade; foreign direct investment